Soluble Epoxide Hydrolase Deletion Limits High-Fat Diet-Induced Inflammation - Wagner, Karen M.; Yang, Jun; Morisseau, Christophe; Hammock, Bruce D. (Frontiers in Pharmacology, 2021)
The soluble epoxide hydrolase (sEH) enzyme is a major regulator of bioactive lipids. The enzyme is highly expressed in liver and kidney and modulates levels of endogenous epoxy-fatty acids which have pleiotropic biological effects including limiting inflammation, neuroinflammation and hypertension. It has been hypothesized that inhibiting sEH has beneficial effects on limiting obesity and metabolic disease as well. There is a body of literature published on these effects, but typically only male subjects have been included. Here we investigate the role of sEH in both male and female mice and use a global sEH knockout mouse model to compare the effects of diet and diet induced obesity. The results demonstrate sEH activity in the liver is modulated by high fat diets in male compared to female mice. In addition, we characterized the sEH activity in high fat content tissues and demonstrated the influence of diet on levels of bioactive epoxy-fatty acids. The sEH KO animals had generally increased epoxy-fatty acids compared to wildtype mice but gained less body weight on higher fat diets. Proinflammatory prostaglandins and triglycerides were also lower in livers of sEH KO mice fed HFD. Thus, sEH activity, prostaglandins and triglycerides increase in male mice on high fat diet but are all limited by sEH ablation. Additionally, these changes also occur in female mice though at a different magnitude and are also improved by knockout of the sEH enzyme.